2018
DOI: 10.5742/mewfm.2018.93341
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Gastric Cancer : A Case Study of Iran

Abstract: Introduction: Cancers have come to be one of the most significant causes of mortality in human societies today. Gastric cancer is more likely to cause more disease and more costs to the patient and the health system of the community. The present study was aimed to evaluate the burden of gastric cancer in Iran, Kohgiluyeh & Boyerahmad province in 2015. Methods: The present descriptive cross-sectional study was conducted in Kohgiluyeh & Boyer-Ahmad Province of Iran in 2015. All 110 patients diagnosed with gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…10 The results of a study showed that the burden of gastric cancer and the number of disability-adjusted life-years in the province of Kohgiluyeh and Boyer Ahmad in 2015 was 754.03 years, indicating a high burden of disease. 11 On the other hand, cancer, especially gastric cancer, in addition to their high burden of disease which leads to a reduction in production and productivity in the economy, imposes heavy costs on households and the health system. These costs are also very important from the societal perspective and account for 5% to 10% of the total health-care costs in most developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…10 The results of a study showed that the burden of gastric cancer and the number of disability-adjusted life-years in the province of Kohgiluyeh and Boyer Ahmad in 2015 was 754.03 years, indicating a high burden of disease. 11 On the other hand, cancer, especially gastric cancer, in addition to their high burden of disease which leads to a reduction in production and productivity in the economy, imposes heavy costs on households and the health system. These costs are also very important from the societal perspective and account for 5% to 10% of the total health-care costs in most developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Although the incidence of GC is gradually decreasing in many regions of Iran, but it is still the most common malignancy in K&B province (6). Based on the official statistics of the Ministry of Health (2015) the number of patients with GC registered in the K&B province has been increasing (25). However, no study is performed at the molecular level to identify the mutation rate of effective genes in GC, such as the R282W P53 mutation in the patients and healthy populations in K&B province.…”
Section: Introductionmentioning
confidence: 99%